2021
DOI: 10.1071/fp21011
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent overexpression of amino acid permease

Abstract: Using pea as our model crop, we sought to understand the regulatory control over the import of sugars and amino acids into the developing seeds and its importance for seed yield and quality. Transgenic peas simultaneously overexpressing a sucrose transporter and an amino acid transporter were developed. Pod walls, seed coats, and cotyledons were analysed separately, as well as leaves subtending developing pods. Sucrose, starch, protein, free amino acids, and endogenous cytokinins were measured during developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…Amino acid transporters are triggered to a greater extent by the applied NH 4 + /NO 3 − ratios in the soil as compared to the hydroponic system. The amino acid profile were influenced by different N application forms, which showed a great impact on the contents of amino acids in different plant parts [ 80 , 81 ]. The most important function of amino acid transporters is the movement of amino acids from source to sink, i.e., plant leaves and seeds to fruits and the exertion of a regulatory mechanism for the uptake of N, the synthesis of amino acids and the allocation of amino acids in plants [ 79 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acid transporters are triggered to a greater extent by the applied NH 4 + /NO 3 − ratios in the soil as compared to the hydroponic system. The amino acid profile were influenced by different N application forms, which showed a great impact on the contents of amino acids in different plant parts [ 80 , 81 ]. The most important function of amino acid transporters is the movement of amino acids from source to sink, i.e., plant leaves and seeds to fruits and the exertion of a regulatory mechanism for the uptake of N, the synthesis of amino acids and the allocation of amino acids in plants [ 79 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid profile were influenced by different N application forms, which showed a great impact on the contents of amino acids in different plant parts [ 80 , 81 ]. The most important function of amino acid transporters is the movement of amino acids from source to sink, i.e., plant leaves and seeds to fruits and the exertion of a regulatory mechanism for the uptake of N, the synthesis of amino acids and the allocation of amino acids in plants [ 79 , 81 ]. Positive feedback of N assimilation helped to increase the N uptake from the solution to roots and roots to shoots due to the applied NH 4 + /NO 3 − ratios and ultimately increased the various types of amino acids in the soil as compared to the hydroponic cultivation system.…”
Section: Discussionmentioning
confidence: 99%
“…In a pea mutant overexpressing SUT1 sucrose transporter and AAP1 amino‐acid transporter, differential expression of PsCWINV1.2 was observed (Grant et al, 2021). Grant et al (2021) also reported co‐upregulated expression of PsCWINV1.2 with a suite of sucrose transporting clade III SWEETs in pea seed coat. Thus, they provided an insight into how PsCWINV1.2 expression in seed coats could be upregulated by a source‐driven influx of sugars and amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sugar flux is partly controlled through the catalytic activity of CWINV localized to the seed coat, determining the magnitude of the transmembrane sucrose gradient. In a pea mutant overexpressing SUT1 sucrose transporter and AAP1 amino‐acid transporter, differential expression of PsCWINV1.2 was observed (Grant et al, 2021). Grant et al (2021) also reported co‐upregulated expression of PsCWINV1.2 with a suite of sucrose transporting clade III SWEETs in pea seed coat.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the study by Kaur et al [ 101 ], which investigated interactions between N and C metabolism, a study was conducted to identify interactions between N and C transport. For this purpose, they first obtained homozygous pea lines overexpressing a sucrose transporter ( PsSUT1 ) or an amino acid transporter ( PsAAP1(3a) ) gebes and then crossed them [ 144 ]. The transgenes contributed to transition of young leaves from sink to source state, and the protein content and seed yield in the double transformants were higher than in the single ones.…”
Section: Genetic Engineering Of Nitrogen Metabolismmentioning
confidence: 99%